Global warming accelerates uptake of atmospheric mercury in regions experiencing glacier retreat - Xun Wang; Ji Luo; Wei Yuan; Che-Jen Lin; (4,5); Feiyue Wang; Chen Liu; Genxu Wang; Xinbin Feng (Journal of Hydraulic Engineering, 2020)
As global climate continues to warm, melting of glaciers releases a large quantity of mercury (Hg) originally locked in ice into the atmosphere and downstream ecosystems. Here, we show an opposite process that captures atmospheric Hg through glacier-to-vegetation succession. Our study using stable isotope techniques at 3 succession sites on the Tibetan Plateau reveals that evolving vegetation serves as an active "pump" to take up gaseous elemental mercury (Hg-0) from the atmosphere. The accelerated uptake enriches the Hg pool size in glacier-retreated areas by a factor of similar to 10 compared with the original pool size in the glacier. Through an assessment of Hg source-sink relationship observed in documented glacier-retreated areas in the world (7 sites of tundra/steppe succession and 5 sites of forest succession), we estimate that 400 to 600 Mg of Hg has been accumulated in glacier-retreated areas (5 parts per thousand of the global land surface) since the Little Ice Age (similar to 1850). By 2100, an additional similar to 300 Mg of Hg will be sequestered from the atmosphere in glacier-retreated regions globally, which is similar to 3 times the total Hg mass loss by meltwater efflux (similar to 95 Mg) in alpine and subpolar glacier regions. The recapturing of atmospheric Hg by vegetation in glacier-retreated areas is not accounted for in current global Hg models. Similar processes are likely to occur in other regions that experience increased vegetation due to climate or land use changes, which need to be considered in the assessment of global Hg cycling.